High-Throughput Data Reveals Novel Circular RNAs via Competitive Endogenous RNA Networks Associated with Human Intracranial Aneurysms - Huang, Qing (Med Sci Monit, 2019)
BACKGROUND: Little is known about epigenetic regulation of intracranial aneurysms (IAs). Circular non-coding RNAs (circRNAs) play crucial roles in cardiovascular diseases, but they have received scant research attention regarding their relationship with IAs. This study aimed to explore new pathological mechanisms of IA through circRNA expression profiles and to provide novel therapeutic strategies. MATERIAL/METHODS: The comprehensive circRNA and mRNA expression profiles were detected by RNA-Seq in human IA walls and superficial temporal arteries (STAs). The RNA-Seq findings were validated by qRT-PCR. GO and KEGG analyses indicated the functions of these circRNAs. A competing endogenous RNA (ceRNA) network was constructed to reveal the circRNA-miRNA-mRNA relationship. Two newly discovered circRNAs were further detected in peripheral blood of IA patients and healthy people to clarify their expression patterns in the periphery. RESULTS: Many differentially expressed circRNAs are closely involved in immune/inflammatory response and cell adhesion/adherens junction. The novel circRNAs (hsa_circ_0072309 and hsa_circ_0008433) regulate DDR2 and MMP2, respectively, which are associated with SMC dysfunction and vascular injury through ceRNA. Moreover, we found differential expression of these 2 circRNAs in the peripheral blood of IA patients, and the expression pattern of hsa_circ_0072309 had central and peripheral consistency. CONCLUSIONS: To the best of our knowledge, this is the first study to perform circRNA sequencing analysis of IAs. hsa_circ_0072309 and hsa_circ_0008433 are novel and pivotal circRNAs related to IAs. This study provides new insights into therapeutic targets and biomarkers for IA patients.